THE ROLE OF DIGITAL MARKETING ON PURCHASE INTENTION AND PURCHASE DECISIONS AT KOPI SI BUDI SURAKARTA - Allouisia Herlina Diventy; Marjam Desma Rahadhini; Rahayu Triastity (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research was conducted at Kopi Si Budi Surakarta and uses a survey method conducted on Kopi Si Budi's Instagram followers. The population of the research is all of Kopi Si Budi's followers. The sampling technique used probability sampling with a simple random sampling of 125 respondents. The analysis technique uses Structural Equation Modeling (SEM). The validity and reliability test uses Confirmatory Factor Analysis (CFA) and Cronbach Alpha. The result shows that social media marketing has no effect on purchase intention. E-word of mouth effect purchase intention. Social media marketing has an effect on purchasing decisions. E-word of mouth has no effect on purchasing decisions. Purchase intention effects purchasing decisions. Social media marketing has an effect on purchasing decisions through purchase intention and e-word of mouth influences purchasing decisions through purchase intention. Keywords: social media marketing, e-word of mouth, purchase intention, and purchase decisions